Genetic Analysis of K-Casein Gene in Milk Protein of Bos Indicus Cattle - Maria Khushbakht, Javed Ahmed Ujan (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Κ-casein, or kappa casein, is a mammalian milk protein involved in several important physiological processes. Chymosin splits K-casein into an insoluble peptide (para kappa-casein) and a water-soluble glycomacropeptide (GMP). GMP is responsible for increased efficiency of digestion, prevention of neonate hypersensitivity to ingested proteins, and inhibition of gastric pathogens. The gene underlying the production of kappa-casein in cow’s Milk shows polymorphisms which affect the amount of protein produced. Higher levels of kappa-casein are associated with increased milk protein and casein content and better cheese yield. Method: The current study aimed to identify the genetic mutations among three indigenous cattle breeds of Sindh, Pakistan. A particular set of primers amplified the targeted area of the K-CASEIN gene after genomic DNA extraction from blood samples of the three cattle breeds, namely Cholistani cattle breed, Tharri, and Sahiwal. Findings: The amplified PCR products were sequenced using the ABI Genetic Analyzer 3500; a BioEdit version 7.2 was used to examine the sequencing data. Using the ensemble gene browser, blast analysis was also performed. Practical Implication: Results revealed 18 mutations in all 03 cattle breeds, including 07 mutations in the Cholistani cattle breed; the Tharri cattle breeds had 06 mutations, and the Sahiwal cattle breeds had 05 mutations. Results of this study of the K-CASEIN gene suggested that Cholistani cattle breeds are more genetically varied than the Sahiwal cattle breeds. Conclusion: Furthermore, the Sahiwal cattle breed is more diverse than the Thari cattle breed for the said gene. Keywords: K-Casein gene, Sahiwal cattle breed, Thari cattle breed, Cholistani cattle breed, Polymorphism